Chocolate‐candy consumption and 3‐year weight gain among postmenopausal U.S. women. (3rd February 2015) - Greenberg, James A.; Manson, JoAnn E.; Buijsse, Brian; Wang, Lu; Allison, Matthew A.; Neuhouser, Marian L.; Tinker, Lesley; Waring, Molly E.; Isasi, Carmen R.; Martin, Lisa W.; Thomson, Cynthia A.
<x xml:space="preserve">Abstract</x> Objective To test the hypothesis that greater chocolate‐candy intake is associated with more weight gain in postmenopausal women. Methods A prospective cohort study involved 107, 243 postmenopausal American women aged 50‐79 years (mean = 60.7) at enrollment in the Women's Health Initiative, with 3‐year follow‐up. Chocolate‐candy consumption was assessed by food frequency questionnaire, and body weight was measured. Linear mixed models, adjusted for demographic, socio economic, anthropomorphic, and behavioral variables, were used to test our main hypotheses. Results Compared with women who ate a 1 oz (∼28 g) serving of chocolate candy <1 per month, those who ate this amount 1 per month to <1 per week, 1 per week to < 3 per week and ≥3 per week showed greater 3‐year prospective weight gains (kg) of 0.76 (95% CI: 0.66, 0.85), 0.95 (0.84, 1.06), and 1.40 (1.27, 1.53), respectively, (P for linear trend<0.0001). Each additional 1 oz/day was associated with a greater 3‐year weight gain (kg) of 0.92 (0.80, 1.05). The weight gain in each chocolate‐candy intake level increased as BMI increased above the normal range (18.5‐25 kg/m2), and was inversely associated with age. Conclusions Greater chocolate‐candy intake was associated with greater prospective weight gain in this cohort of postmenopausal women.